Fundamentación jurídica de la LEX ARTIS sobre el peritaje y el meta peritaje o contra peritaje. - Albuja Quintana, Rodrigo Alejandro (2022)
The present study carries out an in-depth analysis of the legal foundation of the lex artis, its development, fields of application and the lack of a regulatory framework that provides legal certainty to medical professionals, as well as a regulatory framework that provides established parameters so that the expert reports have a broader normative support on which to base themselves and which the judges can have as an instrument with which they can be sure of issuing a well-founded opinion. Some aspects that currently the expert reports do not take for the opinion of validation and good medical practice of a certain professional will be analyzed, it will also be analyzed on the assessment of the expert opinion and the meta expert opinion or against expert opinion within the judicial process, and what aspects are must be taken into account by the judge to remove reasonable doubt within the judicial process. It will be reviewed doctrinally and in legislative matters, statistical aspect in comparative legislation on demands in bad and good medical practice, sociological aspects that the expert report should take into account, as well as a qualifying criticism of the current situation that Ecuador is experiencing with respect to the field of expert reports. In the present investigation, doctrinal documentary analysis was applied, as well as interviews with focus groups of experts through clusters, in order to determine the lack of legal certainty that experts currently maintain regarding their reporting procedure and that cause rights violations, in judicial processes.